Prenatal infection predisposes offspring to enhanced susceptibility to imiquimod-mediated psoriasiform dermatitis in mice - Sebastian Yu; Chia-Wen Lee; Yu-An Li; Tsung-Hsi Chen; Hsin-Su Yu (Wolters Kluwer Medknow Publications, 2022)
Background: Infection can upregulate T helper 17 (Th17) signaling and exacerbate psoriasis. Literature has indicated that prenatal infection induces embryonic development toward Th17 signaling and is a risk factor for developing certain Th17-skewing disorders such as autism in offspring. However, it remains unclear if a prenatal infection is a risk factor for developing psoriasis in offspring. Objectives: We investigated if a prenatal infection predisposes mice offspring to enhanced susceptibility to psoriatic inflammation. Methods: Pregnant C57BL/6 mice were intraperitoneally injected with lipopolysaccharide (LPS) or polyinosinic:polycytidylic acid poly I:C to simulate prenatal bacterial and viral infection, respectively. Phosphate-buffered saline (PBS) injection was used as the control. When mice offspring were at the age of 9-10 weeks, imiquimod (IMQ) cream or control vehicle was applied topically on ears for 5 consecutive days to induce psoriasiform dermatitis. The extent of epidermal hyperplasia and the number of Munro microabscesses were examined by histologic analysis. Protein expressions of neutrophil marker Ly6 g and Th17-associated cytokines were measured by western blotting. Results: Prenatal infection with LPS or poly I:C induced a greater extent of epidermal hyperplasia and more Munro microabscesses after IMQ application as compared with prenatal PBS injection. Mice offspring with prenatal infection also had higher protein expressions of Ly6 g, IL-17a, and interleukin-23 after IMQ stimulation compared with their PBS controls. Conclusion: Prenatal infection predisposes mice offspring to enhanced susceptibility to IMQ-mediated psoriasiform dermatitis. The data obtained from the present animal study suggest that prenatal infection might be a risk factor for developing psoriasis in offspring.